Simulation study for assessment of chemical enhancement and energy consumption of natural gas dehydration processes - Mohamed Abdrabou Mohamed Abdrabou; Shakinaz Taha El Sheltawy; Amr Refay Abdelghany (2024)
Three different TEG flow rates, stripping gas flow rate and reboiler temperature were used for the simulation. Result shows that, the simulation process succeeds in reducing the water content to 2.5lb/MMSCF (Million Standard Cubic Feet of Natural Gas) (40 kg/mmm3) from an initial value of 75lb/MMSCF (1200 kg/mmm3) and achieved 99.24 wt. % of TEG purity without a significant rise in the energy consumption. Using stripping gas to increase triethylene glycol purity and boost the efficiency of the dehydration plant appears to be the best option in the long run.
(3Gf GdZQV ef gPG GdHMK gh OQGSI YedjI GdJLaja ddZGR GdWHjYj Yf WQjb GdGeJUGU HGSJNOGe KdGKj GdGKjdjf Ldjchd hJWhjQ GdfePLI hGdeMGcGI dYedjI JLaja GdZGR GdWHjYj HhGSWI HQfGeL CSHf gGjSjS HGSJNOGe eYGOdI GdMGdI GdJcYjHjI(B. (3gfGc MGLI Gdj JLaja GdZGR GdWHjYj dCRGdI GdejGg GdeQJHWI HGdZGR GdWHjYj aj Tcd HNGQ(B. (3GSJNOeJ GdeMGcGI KdGKI eYOdGJ JOab ef KdGKj GjKdjf GdLdjchd, heYOdGJ JOab ZGR GdfRY , hOQLGJ MQGQI GdZdGjI(B. (3fLM ELQGA GdeMGcGI aj NaV eMJhi GdeGA Edi (B2.5 Ib/MMSCF((3HGhfO dcd edjhf bOe ecYH ef GdZGR(B) (3ef bjeI ChdjI JHdZ (B75 Ib/MMSCF (3hNaV GdWGbI GdeSJgdcI aj YedjI JLaja GdZGR GdWHjYj hGdMUhd Ydj fSHI fbGA ef KdGKj GjKdjf GdLdjchd HYO JfTjWI JUd Gdj (B99.2%.s
Thesis (M.Sc)-Cairo University, 2024.
Bibliography: pages 62-66.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Natural gas processing; Natural gas -- Gas dehydration -- Stripping gas -- TEG regeneration -- Energy consumption